Implementasi Tarbiyah Halaqah pada Wahdah Islamiyah dalam Membentuk Akhlak Pemuda Muslim di Banda Aceh - Arisnaini Arisnaini (2021)
This journal presents research on the importance of Tarbiyah Halaqah Wahdah Islamiyah which can shape Muslim morals. The main discussion is how the contribution of Tarbiyah Halaqah Wahdah Islamiyah in Banda Aceh. This study aims to find out how the implementation of the form of tarbiyah halaqah at Wahdah Islamiyah, in the form of the morals of the youth in Banda Aceh. This research is useful as a contribution of thought in maximizing the potential of Muslim youth. These problems are presented using a normative, pedagogic and sociological theological approach and are presented qualitatively and qualitatively descriptively. Based on the results of the study, it can be seen that the form of implementation of Tarbiyah halaqah through several initial stages of recruitment then followed by group division to be given intensive coaching Wahdah Islamiyah has a major contribution to growing and fostering the morals of Muslim youth in Banda Aceh. This can be seen from the youth who are members of the tarbiyah halaqah to show very positive things to show noble character to Allah SWT. Also to the people around him.